MyoD is essential in rhabdomyosarcoma by promoting survival through differentiation and CYLD - Alexander R. Oles; Peter Y. Yu; Abasi-ama Udeme; Sudarshana Sharma; Priya Londhe; Benjamin R. Pryce; Erin E. Talbert; Eric M. Hill; Carlos J. Miranda; Brian K. Kaspar; Michael A. Arnold; Jack Hyland; et al. (iScience, 2025)
Summary: Rhabdomyosarcoma (RMS) is the most common soft tissue cancer among children, characterized by a skeletal muscle lineage that is impaired from undergoing terminal differentiation. NF-κB is constitutively active in cancer cells and plays a critical role in cell survival. Although NF-κB is also activated in RMS, surprisingly, we find that these tumors are far less dependent on NF-κB for their survival. Instead, RMS cells survive, paradoxically, by being partially differentiated under the control of the myogenic transcription factor MyoD. Loss of MyoD, or cellular reprogramming, dedifferentiates RMS tumor cells and sensitizes their death under stress. MyoD enhances RMS survival by regulating DNA methyltransferases, which in turn suppresses the tumor suppressor and pro-apoptotic gene CYLD. From these findings, we propose that MyoD acts as an oncogene in RMS by enhancing survival through pro-differentiation and anti-cell death activities.